Game of mirrors - Camilleri, Andrea (Camilleri, Andrea. Inspector Montalbano mystery., 2015)
"In Game of Mirrors, Inspector Montalbano and his colleagues are stumped when two bombs explode outside empty warehouses-one of which is connected to a big-time drug dealer. Meanwhile, the alluring Liliana Lombardo is trying to seduce the Inspector over red wine and arancini. Between pesky reporters, amorous trysts, and cocaine kingpins, Montalbano feels as if he's being manipulated on all fronts. That is, until the inspector himself becomes the prime suspect in an unspeakably brutal crime"--